Comparison in Terms of Accuracy between DLP and LCD Printing Technology for Dental Model Printing - Ioannis A. Tsolakis; William Papaioannou; Erofili Papadopoulou; Maria Dalampira; Apostolos I. Tsolakis (MDPI AG, 2022)
Background: The aim of this study is to evaluate the accuracy of a Liquid Crystal Display (LCD) 3D printer compared to a Direct Light Processing (DLP) 3D printer for dental model printing. Methods: Two different printers in terms of 3D printing technology were used in this study. One was a DLP 3D printer and one an LCD 3D printer. The accuracy of the printers was evaluated in terms of trueness and precision. Ten STL reference files were used for this study. For trueness, each STL file was printed once with each 3D printer. For precision, one randomly chosen STL file was printed 10 times with each 3D printer. Afterward, the models were scanned with a model scanner, and reverse engineering software was used for the STL comparisons. Results: In terms of trueness, the comparison between the LCD 3D printer and DLP 3D printer was statistically significant, with a p-value = 0.004. For precision, the comparison between the LCD 3D printer and the DLP 3D printer was statistically significant, with a p-value = 0.011. Conclusions: The DLP 3D printer is more accurate in terms of dental model printing than the LCD 3D printer. However, both DLP and LCD printers can accurately be used to print dental models for the fabrication of orthodontic appliances.